Psychopolitics: Neoliberalism and New Power Techniques - Vatsinas, Andreas (Conatus - Journal of Philosophy, 2017)
Book review of Byung-Chul Han, Psicopolitica: Neoliberalismo y nuevas técnicas de poder (Barcelona: Herder Editorial, 2014).